Heterogenitas Makna Simbolik Atap Masjid Jami’ Pontianak - Rissa , Rissa Fitria Syafutri; Fiska , Fiska Hidayat; Gusti Rahman Adhiarza; Ayu , Tidi Ayu Lestari (Politeknik Negeri Pontianak, 2024)
As a city with high social heterogeneity, historical buildings in Pontianak are inseparable from symbolic elements with diverse meanings. This city began with the arrival of Sultan Syarif Abdurrahman Alqadrie, son of Putri Nyai Tua, a lady-in-waiting in the Matan Kingdom and Al-Habib Husin, who sailed from South Arabia to spread Islam. The Pontianak Jami’ Mosque, which Sultan Abdurrahman founded, was inseparable from the diversity of cultural, political and social elements at that time. This study aims to understand one of the elements of the Jami' mosque building, namely the roof, which is quite dominant in scale proportions. The analysis of the meaning of the mosque's roof uses semiotics by Charles Sanders Pierce and is supported by data from related literature. The study results show that heterogeneity and high tolerance values have long been in the veins of the first building built in Pontianak. The architectural elements of ancient Indonesian mosques, which are full of Islamic values, ​​blend with European architectural symbols, as well as the local values ​​of the Kalimantan region itself.